ELECTRONIC SPORTS (E-SPORTS): A GLOBAL PHENOMENON AFFECTING SPORTS CULTURE - Pasaribu, Ahmad Muchlisin Natas (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This research presents a comprehensive analysis of the psychological and social impacts of participation in eSports, a global phenomenon that has enriched sports culture. Through a literature review approach, this research explores player motivation, online identity, and the mental health impact of playing intensity. In addition, the research integrates cross-cultural dimensions, discussing the interaction of eSports with cultural values in various societies. The results provide deep insights into the complexity of individuals' experiences of eSports and the central role of online communities in shaping social identities. While this research makes important contributions, the limitations of limited primary data, publication age, and cultural representation must be acknowledged. In conclusion, this research underscores that eSports is not only a growing e-sports phenomenon, but also a significant cultural force, shaping norms and values in contemporary sports culture. This research provides a basis for further understanding and points the way for future research that can broaden the scope and deepen the analysis of the impact of eSports on global sports culture.